2022
DOI: 10.3389/fmicb.2022.976154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frequency and amount of stover mulching on soil nitrogen and the microbial functional guilds of the endosphere and rhizosphere

Abstract: Stover mulching as a conservation and sustainable agricultural practice is beneficial for maintaining soil nitrogen (N) requirements and plant health. The microbial functional guilds of the root and rhizosphere are important factors in the soil nitrogen cycle. However, it is unclear how the frequency and amount of stover mulching influence microbial functional guilds in the root and rhizosphere. Therefore, we investigated the responses of the microbial functional guilds in the endosphere and rhizosphere to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…And we found that stover mulching effectively inhibited the relative abundance of bacterial plant pathogen, while F1/3 had the most obvious inhibition among experimental groups. Similarly, literature indicates that F1/3 and F2/3 exhibit the lowest abundance of nitrifying bacteria and anaerobic nitrifying bacteria, the highest abundance of nitrogen-fixing bacteria, and F2/3 significantly reduces the relative abundance of fungi plant pathogens in the rhizosphere ( Song et al, 2022 ). Multiple lines of evidences suggest that frequency but not the quantity of stover mulching plays a dominant role in influencing the microbial communities within the endosphere and rhizosphere.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…And we found that stover mulching effectively inhibited the relative abundance of bacterial plant pathogen, while F1/3 had the most obvious inhibition among experimental groups. Similarly, literature indicates that F1/3 and F2/3 exhibit the lowest abundance of nitrifying bacteria and anaerobic nitrifying bacteria, the highest abundance of nitrogen-fixing bacteria, and F2/3 significantly reduces the relative abundance of fungi plant pathogens in the rhizosphere ( Song et al, 2022 ). Multiple lines of evidences suggest that frequency but not the quantity of stover mulching plays a dominant role in influencing the microbial communities within the endosphere and rhizosphere.…”
Section: Discussionmentioning
confidence: 96%
“…It remains uncertain whether the effects of stover mulching on endophytes and rhizosphere microbiota are merely the extension of its influence on the soil microbial community or if they involve more intricate and unique relationships. Existing studies have indeed assessed the effects of variations in stover mulching frequency and amount on nitrifying bacterial and fungal plant pathogens within both the endosphere and rhizosphere ( Song et al, 2022 ), with some research delving down to the species level ( Wang et al, 2020a , b ). However, there remain substantial gaps in the research on how the quality and frequency of stover mulching influence endosphere and rhizosphere microbial communities, particularly with respect to critical groups such as rhizobia and bacterial plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Both the rhizosphere and endophytic microbial communities are strongly influenced by plant roots, and changes in their composition are closely related to the plant–microbe interactions in response to climate change ( Philippot et al., 2013 ; Song et al., 2022 ; Adeleke et al., 2023 ). As with most ecosystems, the observed rhizosphere microbial diversity was significantly and positively correlated with MAT.…”
Section: Discussionmentioning
confidence: 99%